Pharmacogenomics of β‐Adrenergic Receptors and Their Accessory Signaling Proteins in Heart Failure - Dorn II, Gerald W. (Clin Transl Sci, 2008)
β‐adrenergic receptors (βAR) are widely expressed on cardiovascular cells. Pharmacological stimulation or blockade of βAR signaling is the therapeutic mainstay in cardiogenic shock, hypertension, ischemia, arrhythmias, and heart failure. Interindividual variability in the response to βAR agonists and antagonists has prompted examination of variability in the genes encoding βAR signaling pathway members. Prominent among the genes that have been examined so far in heart failure are the β(1)AR, β(2)AR, and G‐protein‐coupled receptor kinase 5 (GRK5). Each has nonsynonymous polymorphisms that alter amino acid sequence and protein function and regulation in cell‐based systems, genetically altered mouse models, or human hearts. Here, we review these phenotypes and results from published clinical studies, with a focus on heart failure pharmacogenomics. Thus far, very few studies have utilized analogous protocols or drugs, and discrepancies in the clinical studies are apparent. A compelling approach is the use of multiple methods to understand the molecular, cellular, and organ phenotypes of a variant and couple these with clinical studies designed to specifically address the relevance of those phenotypes in humans. Undoubtedly, additional loci will be identified, and together, will provide for genetically driven, individualized treatments for heart failure.